Conocimiento de profesores, padres de familia y escolares sobre salud oral. Sector 2. Riobamba.2021 - Erika Vanessa , Villacres Franco (2022)
ABSTRACT: The degree of knowledge in the oral care and protection of people who included in the family and social environment of early schoolchildren and adolescents takes on preventive importance of oral conditions that affect the normal development of a certain study group. The present investigation focuses on a descriptive, observational, correlational process of horizontal heterocedasticity in an objective manner, allowing an analysis of the level of knowledge about oral health of teachers, parents and schoolchildren, in the Educational Unit "Capitán Edmundo Chiriboga G" and “Milton Reyes Educational Unit”. The study population consisted of 100 students in the second and eighth years of basic general education, 100 parents and 4 professors. The techniques used were surveys and tests; and as instruments the clinical history and questionnaires; the data obtained processed in the statistical program SPSS version 22. The results showed that the ceo-d and community CPO-D index of the students was 4, which means that the population studied maintains a medium risk of carious lesions, while that the plaque indicator reported an acceptable result (14.66%). One aspect to emphasize is that the generalized population is 79%, presenting a slight lack of knowledge about oral care and professors a regular knowledge